HUBUNGAN TINGKAT SPIRITUALITAS DENGAN RESILIENSI PADA WARGA BINAAN PEMASYARAKATAN (WBP) DI LEMBAGA PEMASYARAKATAN (LAPAS) KELAS IIA TANGERANG - Ayu Safitri; Siti Rochmani; Lastri Mei Winarni (Nusantara Hasana Berdikari, 2022)
Prisoners who enter prisons will have psychological problems, such as anxiety, and worry, but if the intensity experienced is too high it will interfere with effectiveness and form negative emotions, this condition causes the inmates to be not resilient. The success of correctional inmates to obtain a resilient life by increasing spirituality, namely the feeling of being connected to something bigger than ourselves and trying to find meaning in life and our belief that something bigger than us will help us. The purpose of this study is to determine the relationship between spirituality level and resilience in inmates in prisons Class II A Tangerang. This research method uses descriptive quantitative research with a cross sectional research design. The study was conducted in Lapas Class IIA Tangerang in June-August 2022. The population in this study amounted to 314 WBP, the sampling technique used was accidental sampling with the number of samples taken was 155 WBP. Data were collected using a questionnaire and analyzed with the Spearmank rank test. Based on the analysis, it was found that the P value was 0.001 (P < 0.05), which means H0 is rejected and Ha is accepted, meaning that there is a relationship between spirituality level and resilience in Correctional Inmates in Class IIA Tangerang Prison. The conclusions and suggestions in this study are that spirituality greatly affects a person's resilience so it is hoped that prison officers can provide psychological support, and from nursing practice they can provide nursing care with spiritual support.